2012
DOI: 10.1016/j.bjoms.2010.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and pathology: a macrophage account

Abstract: Macrophages are present in healthy oral mucosa and their numbers increase dramatically during disease. They can exhibit a diverse range of phenotypes characterised as a functional spectrum from pro-inflammatory to anti-inflammatory (regulatory) subsets. This review illustrates the role of these subsets in the oral inflammatory disease lichen planus, and the immunosuppressive disease oral squamous cell carcinoma (SCC). We conclude that the role of macrophages in driving progression in oral disease identifies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 54 publications
0
31
1
Order By: Relevance
“…Taken together, these findings indicate the pro-tumor profile of M2 macrophages since this phenotype promotes angiogenesis and extracellular matrix remodeling by expressing metalloproteinases, conditions that favor neoplastic dissemination. 12,14,15,17,19,22 In contrast to previous studies on OSCC, the present results suggest that M2 TAMs may play a more important role in early stages of lip carcinogenesis. During these stages in which tumors are possibly more immunogenic, neoplastic cells may promote an immunosuppressive microenvironment in order to escape immune surveillance.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Taken together, these findings indicate the pro-tumor profile of M2 macrophages since this phenotype promotes angiogenesis and extracellular matrix remodeling by expressing metalloproteinases, conditions that favor neoplastic dissemination. 12,14,15,17,19,22 In contrast to previous studies on OSCC, the present results suggest that M2 TAMs may play a more important role in early stages of lip carcinogenesis. During these stages in which tumors are possibly more immunogenic, neoplastic cells may promote an immunosuppressive microenvironment in order to escape immune surveillance.…”
Section: Discussioncontrasting
confidence: 55%
“…This immunosuppressive capacity is a consequence of the production of anti-in flammatory and immunosuppressive cytokines such as IL-10 and transforming growth factor beta (TGF-β), inhibition of the inflammatory and cytotoxic functions of M1 macrophages, and induction of angiogenesis and tissue remodeling and repair, conditions that favor tumor growth and dissemination. 12,13,14,15,16,17,18,19,20,21,22 Although studies have suggested a significant association between TAMs and poor prognosis in patients with oral squamous cell carcinoma (OSCC), 14,15,23,24,25,26 little is known about these macrophage phenotypes in SCCLL. Therefore, the objective of the present study was to investigate the presence of TAM subpopulations M1 and M2 in cases of SCCLL and to evaluate the possible role of these subtypes in the development of regional lymph node metastasis and their association with clinical and pathological features of the tumor.…”
mentioning
confidence: 99%
“…As the lesion progresses, increasing numbers of mononuclear cells emigrate into the affected tissues and into the subgingival sulcus, consistent with a more chronic inflammatory lesion (Smith, Seymour and Cullinan, 2010). The cellular profiles of these apparent established lesions include various phenotypes of T cells, B cells and plasmacytes producing antibody (Ebersole, Dawson, Morford, Peyyala, Miller and Gonzalez, 2013), and antigen-presenting cells including macrophages (Hajishengallis, 2010, Bartold, Cantley and Haynes, 2010, Merry, Belfield, McArdle, McLennan, Crean and Foey, 2012) and dendritic cells [DC, (Anjana, Joseph and Suresh, 2012, Cutler and Teng, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…They are present in the healthy oral mucosa and in larger numbers during pathological processes. 11 Macrophages are classified as M1 (pro-inflammatory) and M2 (antiinflammatory) according to the functions of their effectors. 12 It has been postulated that M1 macrophages present in OLP might contribute to exacerbation of manifestations of the disease through the production of pro-inflammatory agents such as tumour necrosis factor alpha (TNF-α) and interleukin-1b (IL-1b).…”
Section: Discussionmentioning
confidence: 99%